Fine mapping and identification of the gene Cla019481 responsible for patches at the hilum on the testa of watermelon seeds - Lv, Runbu; Zhou, Dan; Liu, Hongyuan; Xie, Chengyuan; Zhang, Yufu; Zhang, Xiaoyu; Li, Dongye; Ma, Shuangwu; Chen, Jifeng (Frontiers in Plant Science, 2025)
The presence or absence of patches at the seed hilum is a valuable phenotypic marker for breeding new cultivars and identifying watermelon germplasm resources, although the candidate gene regulating this trait remains unknown. In this study, the F1 generation seeds (with patches at the hilum) were derived from a cross between the female parent (no patches at the hilum) and the male parent (with patches at the hilum), and a back cross (BC) population was generated by crossing F1 with the female parent. The segregation ratio of the patches and no-patches trait conforms to the expected 1:1 Mendelian ratio in the BC population. Restriction-site–associated DNA sequencing was performed on the BC population to construct a high-density genetic map. The analysis revealed a major quantitative trait locus (QTL) on chromosome 3, spanning 5,375,019–5,784,364 bp and harboring 35 annotated genes from Cla019451 to Cla019485, which govern the stably inherited trait of patches at the hilum on the testa of watermelon seeds. A reliable derived cleaved amplified polymorphic sequence (dCAPS) marker was developed within the interval, demonstrating perfect genotype–phenotype co-segregation. Consequently, the target QTL was delimited to a 40-kb region on chromosome 3, which contains the candidate gene Cla019481 for patches at the hilum. Insertions/deletions (Indel) and single-nucleotide polymorphisms (SNPs) indicated that Cla019481 was the top candidate gene responsible for the presence or absence of patches at the hilum. Based on dCAPS marker development for SNP genotype identification and visual phenotype classification across different groups of watermelon accessions, no phenotypic inconsistencies were observe in materials lacking patches at the hilum. In other words, the genotype indicated absence of patches at the hilum, and the phenotype corresponded accordingly in the tested materials. Gene expression validation experiments using materials with/without patches at the hilum, combined with quantitative RT-PCR (qRT-PCR), revealed a positive correlation. Elevated Cla019481 expression coincided with progressive darkening of hilum pigmentation during the three seed development stages (8, 18, and 25 days after flowering). The verification test results demonstrate that Cla019481 expression critically regulates hilum formation. Cla019481 thus plays a significant role in the presence of patches at the hilum on watermelon seeds.